The effect of light resistance training using dumbbells and ankle-wrist weights on modifiable cardiovascular disease risk factors - Yaacob, Najib Majdi (2013)
Cardiovascular diseases which account for the majority of the population disease burden are closely linked to unhealthy lifestyles. One of the global strategies to reduce the burden is by promoting physical activity which includes both aerobic activity and resistance training. Resistance training is an important component of physical activity which has a great potential for improvement of overall health. This study aimed to determine and compare the effect of light resistance training using either dumbbells or ankle-wrist weights on body composition, blood pressure, health related physical fitness and biochemical parameters among overweight and obese adults in Kelantan. One hundred and thirty eight overweight and obese adults, aged 18-60 years were randomized to two groups; dumbbell group (n=69) and ankle-wrist weight group (n=69). Participants in dumbbell group performed group exercises three times per week using a pair of one kilogram dumbbells. The exercise consisted of a one sets of 12 movements, 12 repetitions for each movements which lasted for 20 minutes. Participants in ankle-wrist weight groups were given a pair of 500 gm ankle and a pair of 500 gm wrist weights to be used during activities of daily living for at least 20 minutes, three days per week. For both groups, resistances training for the first three months were closely monitored for adherence and the last three months were not directly monitored. Eighty nine participants completed this sixth month study. At third month, both groups showed significant reduction from baseline in waist circumference (WC) (dumbbell group: mean difference: 4.26, 95% CI: 2.10, 6.42; p<0.001; ankle-wrist weight group: mean difference: 3.31, 95% CI: 2.07, 4.55; p<0.001), waist to hip ratio (WHR) (dumbbell group: mean difference: 0.022,95% CI: 0.003, 0.041; p—0.016; ankle-wrist weight group: mean difference: 0.011, 95% CI: 0.001, 0.022; p—0.035) body fat percentage (dumbbell group: mean difference: 1.14, 95% CI: 0.60, 1.68; p<0.001; ankle-wrist weight group: mean difference: 1.20, 95% CI: 0.72, 1.69; p<0.001) and significant increase in skeletal muscle percentage (dumbbell group: mean difference: -0.66, 95% CI: -1.06, -0.27; p<0.001; ankle-wrist weight group: mean difference: -0.82, 95% CI: -1.13, -0.51; p<0.001), cardiorespiratory fitness (dumbbell group: mean difference: 17.23, 95% CI: 14.63, 19.83; p<0.001; anklewrist weight group: mean difference: 15.57, 95% CI: 13.18, 17.96; p<0.001), muscular endurance (Push up test: dumbbell group: mean difference: -5.78, 95% CI: -7.04, -4.51; p<0.001; ankle-wrist weight group: mean difference: -5.41, 95% CI: - 6.48, -4.34; p<0.001; Sit up test: dumbbell group: mean difference: -8.33, 95% CI: - 10.18, -6.47; p<0.001; ankle-wrist weight group: mean difference: -8.96, 95% CI: - 10.46, -7.46; p<0.001), muscular strength (Handgrip strength: dumbbell group: mean difference: -6.30, 95% CI: -8.77, -3.83; p<0.001; ankle-wrist weight group: mean difference: -4.16, 95% CI: -5.51, -2.82; p<0.001; Leg strength: dumbbell group: mean difference: -16.43, 95% CI: -19.84, -13.02; p<0.001; ankle-wrist weight group: mean difference: -21.49, 95% CI: -25.89, -17.09; p<0.001) and flexibility (dumbbell group: mean difference: -5.40, 95% CI: -6.63, -4.17; p<0.001; ankle-wrist weight group: mean difference: -1.67, 95% CI: -2.40, -0.95; p<0.001). Participants in dumbbell group showed significant reduction in total cholesterol (mean difference: 0.30, 95% CI: 0.03, 0.57; p=0.033), low density lipoprotein cholesterol (LDL-C) (mean difference: 0.36, 95% CI: 0.09, 0.63; p=0.004) and non-high density lipoprotein cholesterol (mean difference: 0.39, 95% CI: 0.12, 0.66; p=0.002) while participants in ankle-wrist weight group showed significant increase in high density lipoprotein cholesterol (HDL-C) (mean difference: -0.14, 95% CI: -0.25, -0.02; p=0.014) at the end of the third month. At the end of sixth month, significant reduction from baseline in WC and WHR, and significant increase in cardiorespiratory fitness, muscular strength, muscular endurance and flexibility were maintained with addition of significant reduction of systolic blood pressure (SBP) for both groups (dumbbell group: mean difference: 5.60, 95% CI: 1.24, 9.96; p=0.006; ankle-wrist weight group: mean difference: 5.27, 95% CI: 0.99, 9.54; p=0.008) and significant increase in HDL-C were maintained for ankle-wrist weight group. After adjustment of age only improvement of WC, SBP, cardiorespiratory fitness, muscular strength, muscular endurance and flexibility were still significant. Effect of six months light resistance training between using dumbbells and ankle-wrist weights were similar with exception of leg strength which was better in ankle-wrist weight group (at month 3: 62.38 vs. 68.43; at month 6: 58.38 vs. 70.96; p<0.001) and flexibility was better for dumbbell group (at month 3: 36.70 vs. 32.59; at month 6: 37.83 vs. 33.35; p<0.001). Resistance exercise using either dumbbells or ankle-wrist weight produce significant improvement in certain components of body composition, blood pressure, health related physical fitness and biochemical parameters. Light resistance training should be considered to be an integral component of healthy lifestyle promotion programs aiming to reduce cardiovascular risk and to improve overall health.